The Rule And Status of Women in the Indigenous Igala Religion - Okala Yunusa Yusufu; Amodu Salisu Ameh; Muraina Kamilu Olanrewaju (Indonesian Gender and Society Journal, 2023)
This research discusses the issue of the role and status of women in the Igala tribe's traditional religions. This research aims to deeply analyze the beliefs, practices, and norms that shape the rules and status of women in the Igala tribe's indigenous religions by using a qualitative descriptive approach. The research design used is a case study. The subjects of this study were Igala women involved in religious practices, with a test subject of 30 women’s who acted as priests, fortune tellers, and community leaders. Data were collected through in-depth interviews, participatory observation, and document analysis, with the research instruments being interview guidelines and observation notes. Data analysis was conducted using the thematic analysis method. The results showed that Igala women are essential in religious practices and have significant spiritual authority. This study concludes that Igala women have complex and diverse roles in their indigenous religion, reflecting the interconnectedness between humans, nature and spirituality. The implications of this study show the importance of empowering women in their religious roles to preserve the cultural and spiritual heritage of the Igala people.